2007
DOI: 10.1051/0004-6361:20078412
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of VHE γ-rays from the distant BL Lacertae 1ES 0347-121

Abstract: Aims. Our aim is to study the production mechanism for very-high-energy (VHE; >100 GeV) γ-rays in distant active galactic nuclei (AGN) and use the observed VHE spectrum to derive limits on the Extragalactic Background Light (EBL). We also want to determine physical quantities through the modeling of the object's broad-band spectral energy distribution (SED). Methods. VHE observations (∼25 h live time) of the BL Lac 1ES 0347-121 (redshift z = 0.188) were conducted with the High Energy Stereoscopic System (HESS)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(39 citation statements)
references
References 29 publications
6
33
0
Order By: Relevance
“…This locates their Compton peak in the SED assuredly above 2-10 TeV, the highest Compton-peak energies ever seen in blazars (e.g. Aharonian et al 2006Aharonian et al , 2007bAcciari et al 2009Acciari et al , 2010b. This is different from all the other VHE-detected HBL, and in particular those bright in Fermi, which are characterized by steep intrinsic VHE spectra (ΓVHE > 2) and Compton peak energies around ∼ 100 − 200 GeV.…”
Section: Introductionmentioning
confidence: 73%
“…This locates their Compton peak in the SED assuredly above 2-10 TeV, the highest Compton-peak energies ever seen in blazars (e.g. Aharonian et al 2006Aharonian et al , 2007bAcciari et al 2009Acciari et al , 2010b. This is different from all the other VHE-detected HBL, and in particular those bright in Fermi, which are characterized by steep intrinsic VHE spectra (ΓVHE > 2) and Compton peak energies around ∼ 100 − 200 GeV.…”
Section: Introductionmentioning
confidence: 73%
“…The H.E.S.S. telescopes first discovered a VHE γ-ray emission from this source in 2006 above an energy threshold of 250 GeV [71]. The observed differential photon spectrum was described by a power law with a spectral index of 3.10±0.23 and no evidence of short term variability on monthly timescales was observed.…”
Section: Es 0347-121mentioning
confidence: 99%
“…Such IHL model was suggested by Cooray et al (2012b) to explain the observed fluctuation of the EBL. The spatial fluctuations of the EBL were observed by CIBER (Zemcov et al, 2014), AKARI (Matsumoto et al, 2011), and Spitzer (Kashlinsky et al, 2005, 2007, 2012) from 1.1 to 4.5 µm in order to avoid uncertainty of the ZL model, since the ZL is known to be spatially smooth (Pyo et al, 2012). The observed fluctuations are consistent with each other and show significant large fluctuations at angular scales larger than 100 arcsec, which cannot be explained by known foreground emission.…”
Section: What Is Origin Of Ebl Excess?mentioning
confidence: 99%
“…Results from TeV-γ blazars are problems for the extragalactic origin of the EBL, since a high NIR EBL level makes intergalactic space opaque to TeV-γ photons (Dwek et al, 2005b;Aharonian et al, 2006Aharonian et al, , 2007Mazin & Raue, 2007;Raue et al, 2009). However, a recent discovery of a high redshift (z> 0.6) blazar (Furniss at al., 2013) contradicts the standard scenario above, and it requires a new physical process, such as the secondary TeV γ-ray model (Essey & Kusenko, 2010) or the Axion-like particles model (Sánchez-Conde et al, 2007).…”
Section: What Is Origin Of Ebl Excess?mentioning
confidence: 99%